Importancia de los aminoácidos en la agricultura bajo condiciones de estrés abiótico - Castillo Sánchez, Eddy Javier (2022)
This bibliographic review deals with the importance of amino acids in agriculture under conditions of abiotic stress. It should be noted that the application of free amino acids accelerates the tolerant response of crops to abiotic stress, reducing yield losses caused by stress; In addition, the applications of amino acids to the crop have rapidly visible responses, with more vigorous crops being observed. The conclusions determine that the main amino acids in agriculture are L-glutamic, L-glycine and L-aspartic acid, L-alanine, L-arginine, since they promote photosynthesis, salinity, nutrient absorption and pollination, to improve plantations and amino acid applications are made when plants are stressed due to different abiotic factors such as mechanical damage, diseases, temperatures, in order to avoid yield reductions.